Psikologi Agama Terhadap Perubahan Perilaku Anak Akibat Permainan Kartu UNO di MI - Muis, M.; Dewi, Rosa (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This type of research uses a qualitative descriptive research method to find out what is happening in the research environment, namely at MI Persmin, Wonokromo Surabaya. By collecting interview data and case studies in the field. This qualitative description is balanced by analysis and interpretation with the goal of data analysis being to organize the description in a way that makes it controllable. Problems that occur in educational institutions or at the elementary school/Madrasah Ibtidaiyah Persmin, Wonokromo Surabaya. Students play UNO card games during lessons or when the teacher is not in class and sometimes UNO card games are played during recess. As a result of this UNO Card game, students experience social deviations such as changes in lazy behavior while studying and not listening to the teacher during the lesson, inviting their colleagues to play UNO Cards. The results of research on the Psychology of Religion on Changes in Children's Behavior Due to the UNO Card Game in MI. There are several things related to the review of the psychology of religion, namely from family education. Because the most important thing is the family environment in obtaining children's education and behavior so that the process of forming behavior is the role of the family, namely parents and Islamic education have an important role and responsibility for coaching, guidance, development and directing the potential of children so that they function and play a role. as the essence of the incident.